THE RELATIONSHIP BETWEEN TEACHERS’ ABILITY IN MANAGING CLASS AND STUDENTS’ MOTIVATION WITH STUDENTS’ OUTCOMES IN FIQH CLASS AT MDTA BABUL ULUM MEDAN - Khairunnisah Khairunnisah; Mardianto Mardianto; Khadijah Khadijah (UIN Sumatera Utara Medan, 2021)
This study aims to find out the relationship between the ability of teachers to manage the classroom, students’ motivation in learning and its significance to the learning outcomes of Fiqh at MDTA Babul Ulum Medan. This research follows quantitative research with survey method. The population of this study consists of all students of MDTA Babul Ulum Medan, 170 people, with a sample taken 15% of the population, namely 26 fourth grade students. The data were collected using a questionnaire for further correlation analysis. The findings of this study indicate that there is a significant relationship between the ability of teachers to manage the classroom with Fiqh learning outcomes with a correlation of 0.706, and there is a significant relationship between learning motivation and learning outcomes with a correlation of 0.719. as well as a significant relationship between the ability of teachers to manage the classroom and learning motivation simultaneously on learning outcomes of fiqh with a correlation of 0.792.